BENCANA ALAM DAN PENDIDIKAN INTERPROFESI - Wiwik Kusumawati (Pharmaciana, 2015)
Health care provider provide first response to patients in disaster. Medical and health institutions in Indonesia which produce health professional are still in early process to develop IPE for their students. Health professional unaccustomed with team work to serve patients, therefore they are not properly prepared to response natural disasters. The aim of this article is to give understanding for health institutions about interprofessional education (IPE) concept related to natural disaster. Review article conducted by analyzing scientific article from journals and text books. IPE is a necessary step in preparing a collaborative practice ready health work force to respond in disaster and getting better patient outcomes. Patients are the primary focus of any emergency response such as disaster. In disaster team work is the crucial competency that must be think first. Team performance however may not be optimal and it is often the patient who suffers from this dysfunction. Improved inter professional practice in emergency response will lead to better patient outcomes when teams have adequate knowledge and skills. They will manage the patients each other appropriately based on their each role. Health institutions should develop IPE including module focus on disaster/emergency preparedness to optimize role of health provider. Real experience into community exercises also necessary to ensure that student involvement during actual disasters also needed as a part of local disaster management plans.